Emotion, Politics and Society - Thompson, Simon. author. aut Link
IX, 192 p.
Keywords: This timely book critically addresses the intersection between power, politics and emotions. Challenging traditional dichotomies which counterpose rationalist to non-rationalist epistemologies, it offers a sustained argument for a more complete and integrated rationalism and helps us understand emotions in contemporary social and political life.